2002
DOI: 10.2460/javma.2002.220.1020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transdermal administration of fentanyl versus intramuscular administration of butorphanol for analgesia after onychectomy in cats

Abstract: Our data did not reveal a difference in pain relief between administration of TDF and butorphanol. Plasma cortisol concentrations were not different between groups. Fentanyl appeared to provide equivalent analgesia to butorphanol in cats undergoing onychectomy. The primary advantage of using a TDF patch is that repeated injections are not required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 16 publications
3
71
0
2
Order By: Relevance
“…Η τοποθέτηση εμπλάστρου φαιντανΰλης, με ρυθμό αποδέσμευσης 25 μg/h πριν από τη χειρουργική επέμβαση, εξασφαλίζει ικανοποιητική αναλγησία, όπως προκύπτει από τις δια κυμάνσεις της συγκέντρωσης της κορτιζόλης και της γλυκόζης στο αίμα (Glerum et al 2001). Ακόμη, παρέ χει καλύτερη αναλγησία και μικρότερη καταστολή, συ γκρινόμενη με την ενδομυϊκή χορήγηση βουτορφανό-λης ανά 4 ώρες μετεγχειρητικούς (Franks et al 2000), ενώ παρουσιάζει και το πρόσθετο πλεονέκτημα της αποφυγής των επαναλαμβανόμενων ενδομυϊκών εγ χύσεων (Gellasch et al 2002). Ανιχνεύσιμα επίπεδα φαιντανΰλης στο αίμα παραμένουν επί 18 έως 20 ώρες μετά την απομάκρυνση του εμπλάστρου (Lee et al 2000).…”
Section: οπιοειδήunclassified
See 1 more Smart Citation
“…Η τοποθέτηση εμπλάστρου φαιντανΰλης, με ρυθμό αποδέσμευσης 25 μg/h πριν από τη χειρουργική επέμβαση, εξασφαλίζει ικανοποιητική αναλγησία, όπως προκύπτει από τις δια κυμάνσεις της συγκέντρωσης της κορτιζόλης και της γλυκόζης στο αίμα (Glerum et al 2001). Ακόμη, παρέ χει καλύτερη αναλγησία και μικρότερη καταστολή, συ γκρινόμενη με την ενδομυϊκή χορήγηση βουτορφανό-λης ανά 4 ώρες μετεγχειρητικούς (Franks et al 2000), ενώ παρουσιάζει και το πρόσθετο πλεονέκτημα της αποφυγής των επαναλαμβανόμενων ενδομυϊκών εγ χύσεων (Gellasch et al 2002). Ανιχνεύσιμα επίπεδα φαιντανΰλης στο αίμα παραμένουν επί 18 έως 20 ώρες μετά την απομάκρυνση του εμπλάστρου (Lee et al 2000).…”
Section: οπιοειδήunclassified
“…Σε κλινικές συνθήκες, συνήθως χορηγεί ται κάθε τέσσερις ώρες σε δόση 0,2 mg/kg σ.β. (Franks et al 2000, Gellasch et al 2002. Συχνά, σε συνδυασμό με άλλα φάρμακα, όπως π.χ.…”
Section: οπιοειδήunclassified
“…Objective physiologic measurements such as increases in heart rate and respiratory rate, increased mean arterial blood pressure and pupil dilation, and increased plasma cortisol concentrations have not been demonstrated as sensitive demarcations between nonpainful and painful animals (dogs and cats) as a means to assess severity of pain (70)(71)(72). These changes in physiologic measurements are not specific pain indicators and may also be associated with physical exertion, fever, and anxiety (73).…”
Section: University Of Melbourne Pain Scalementioning
confidence: 99%
“…Reptiles have integument layers arranged similarly to mam mals. Although the scale (stratum germinivatum) layer is the thickest layer, it is also lipid-soluble; so, systemic fentanyl absorption should occur via the transdermal route (Rossi, 1996;Glerum et al, 2001;Gellasch et al, 2002), as occurs with mammals. Time to reach systemic fentanyl concentrations associated with clinical analgesia will vary by individual, by species, ambient heat, and thickness and health o f the skin (Riviere and Papich, 2001;Ashburn et al, 2003;Mills et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in small animal practice (Kyles et al, 1996;Glerum et al, 2001;Gellasch et al, 2002;Hoffmeister and Egger, 2004) and research settings for large domestic and exotic mammals (Grubb et al, 2005), transdermal fentanyl (TDF) patches (Duragesic, Janssen Pharmaceutica, Titusville, New Jersey) have been used as means of analgesia. Although in hum an medicine the primary indication for T D F is chronic, nonoperative pain (Konishi et al, 2005), it has been demonstrated clinically effective for control of peri-operative pain in cats, Felis sylvaticus (Lee et al, 2000;Glerum et al, 2001;Gellasch et al, 2002;Davidson et al, 2004); shown to achieve analge sic systemic concentrations in rabbits, Oryctolagus cuniculus (Foley et al, 2001) and dogs, Canis familiaris (Kyles et al, 1996); and more recently applied in acute (Pasero, 2005) and operative (Koo, 2005) pain control for humans.…”
Section: Introductionmentioning
confidence: 99%